A One Health Approach Molecular Analysis of Staphylococcus aureus Reveals Distinct Lineages in Isolates from Miranda Donkeys (Equus asinus) and Their Handlers - Silva, Vanessa (2022)
Donkeys (Equus asinus) are in decline in Europe. Occupational exposure to farm animals has been associated with increased staphylococci carriage. We aimed to isolate S. aureus and coagulase-negative staphylococci (CoNS) from donkeys and handlers and characterize the antimicro-bial resistance profiles and genetic lineages of S. aureus strains. Oral and nasal swab samples were collected from 49 Miranda donkeys and 23 handlers from 15 different farms. Staphylococci species were identified by MALDI-TOF MS. The presence of antimicrobial resistance genes and virulence factors was investigated by PCR. Molecular typing was performed in S. aureus isolates. From the 49 donkey samples, 4 S. aureus (8.2%) and 21 CoNS (42.9%) were isolated. Ten handlers (43.5%) were carriers of S. aureus and 4 (17.4%) carried CoNS. The CoNS isolates showed resistance to several classes of antimicrobials encoded by the mecA, aph (3′)-IIIa, ant (4′)-Ia, tetM, tetK, lnuA, ermB, ermC, dfrA and dfrG genes. S. aureus isolates were resistant to penicillin, aminoglicosides and tetracycline harboring the blaZ, aph (3′)-IIIa, tetL, tetM and tetK genes. All S. aureus isolates from donkeys belonged to ST49 and spa-type t208 while the strains isolated from the handlers were ascribed to 3 STs and 7 spa-types. However, human isolates were from different STs than the donkey isolates. Donkeys are mainly colonized by methicillin-resistant S. sciuri. S. aureus transmission between donkeys and their handlers appears not to have occurred since the isolates belonged to different genetic lineages.